Math, asked by atahar18viratian22, 2 months ago

A real-valued function f satisfies the relation
f(x)f(y)= f(2xy +3) +3f(x+y)-3f(y)+6y, for all real numbers x and y.
Then the value of f(8) is___​

Answers

Answered by mathdude500
7

\large\underline{\sf{Solution-}}

Given that,

A real-valued function f satisfies the relation

f(x) f(y) = f(2xy +3) + 3 f(x+y) - 3f(y) + 6y, for all real numbers x and y.

Now,

\rm :\longmapsto\:f(x)f(y) = f(2xy +3) +3f(x+y)-3f(y)+6y

On substituting x = 0 and y = 0, we get

\rm :\longmapsto\:f(0)f(0) = f(3) +3f(0)-3f(0)+0

\bf :\longmapsto\:f(0) {}^{2}  = f(3) -  -  - (1)

Now, again Consider,

\rm :\longmapsto\:f(x)f(y) = f(2xy +3) +3f(x+y)-3f(y)+6y

On substituting y = 0, we get

\rm :\longmapsto\:f(x)f(0) = f(3) +3f(x)-3f(0)+0

\rm :\longmapsto\:f(x)f(0) =  {f(0)}^{2}  +3f(x)-3f(0) \:  \:  \:  \:  \{ \: using \: (1) \:  \}

\rm :\longmapsto\:f(x)f(0) -  {f(0)}^{2}   = 3f(x)-3f(0)

\rm :\longmapsto\:[f(x) -  f(0)] f(0) = 3(f(x)-f(0))

So,

\bf\implies \:f(0) = 3 -  -  - (2) \:  \:  \: as \: f(x) \:  \ne \: f(0)

Now, again Consider,

\rm :\longmapsto\:f(x)f(y) = f(2xy +3) +3f(x+y)-3f(y)+6y

On substituting, x = 0 and y = 3, we get

\rm :\longmapsto\:f(0)f(3) = f(3) +3f(3)-3f(3)+18

\rm :\longmapsto\:3f(3) = f(3)  + 18 \:  \:  \:  \:  \:  \:  \{using \: 2) \}

\rm :\longmapsto\:3f(3)-f(3) = 18 \:  \:  \:  \:  \:  \:

\rm :\longmapsto\:2f(3) = 18 \:  \:  \:  \:  \:  \:

\bf :\longmapsto\:f(3) =9 -  -  -  - (3)

Now, Again Consider,

\rm :\longmapsto\:f(x)f(y) = f(2xy +3) +3f(x+y)-3f(y)+6y

On substituting x = 0 and y = 8, we get

\rm :\longmapsto\:f(0)f(8) = f(3) +3f(8)-3f(8)+48

\rm :\longmapsto\:3f(8) = 9 +48

\rm :\longmapsto\:3f(8) = 57

\bf :\longmapsto\:f(8) = 19

Hence,

 \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \purple{ \underbrace{ \boxed{ \blue{ \bf \: f(8) = 19 \:  \: }}}}

Answered by mehulkumarvvrs
0

f(x)f(y)=f(2xy+3)+3f(x+y)-3f(y)+6y

Putting\ x=y=0

We\ get,\ f(0)f(0)=f(3)+3f(0)-3f(0)+6y

Or,\ \ \ \ \ \ f^{2} (0)=f(3)

Putting\ y = 0

We\ get,\ f(x)f(0)=f(3)+3f(x)-3f(0)

Or,\ \ \ \ \ \ f(x)f(0)=f^{2}(0)+3f(x)-3f(0)

Either,\ f(x)-f(0)=0\ or,\ f(0)-3=0

Since\ all\ functions\ cannot\ have\ the\ same\ value, f(0)=3.

Putting \ x=0, y=3

We\ get,\ f(0)f(3)=f(3)+3f(3)-3f(3)+18

Or,\ \ \ \ \ \ f(0) f(3) = f(3) + 3f(3) -3f(3) +18 = f(3) +18

Or,\ \ \ \ \ \ 3 f(3) = f(3) + 18

Therefore, f(3) =9

Putting\ x=0, y=8

We\ get,\ f (0) f (8) = f (3) + 3f (8) - 3f (8) + 48

Or,\ \ \ \ \ \ 3f(8) = f(3) + f(8) -f(8) + 48

Or, \ \ \ \ \ \ 3 f(8) = 9 + 48.

Or,\ \ \ \ \ \ f(8) = 19

The\ question\ is\\''A\ real-valued\ function\ f\ satisfies\ the\ relation\\f(x)f(y) = f(2xy + 3) + 3f(x + y) - 3f(y) + 6y,\\ for\ all\ real\ numbers\ x\ and\ y, then\ the \ value\ of\ f(8)\ is''

Hence, the\ answer\ is\ 19

Hope u liked my solution

Pls mark me as brainliest

Thanks

Similar questions